Bronchoalveolar Lavage Cytology Characteristics and Seasonal Changes in a Herd of Pastured Teaching Horses - Davis, Kaori Uchiumi; Sheats, Mary Katherine (Frontiers in Veterinary Science, 2019)
Equine asthma syndrome (EAS) is a common problem that affects horses of any age. Severe EAS is reported to affect 10-20% of adult horses in the northern hemisphere, while mild/moderate EAS is reported to affect 60-100% of adult horses, depending on the population and geographic region. For both severe and mild/moderate EAS, the presence of lower airway inflammation is attributed to airborne “triggers” such as dust, mold and bacterial components that horses encounter in hay and stable-environments; and treatment recommendations for horses with EAS often include full-time pasture turnout. The caveat to this recommendation is horses with summer-pasture associated EAS (SP-EAS), who experience allergic lower airway inflammation when exposed to summer pasture. The prevalence of EAS in horses on pasture that do not have SP-EAS has not been reported. The purpose of this study was to use bronchoalveolar lavage (BAL) cytology to determine the prevalence of EAS in a herd of pastured, adult research horses with no history of respiratory disease. The horses were members of a teaching animal herd housed on pasture in the southeastern United States and fed round-bale Bermuda-grass hay. BAL fluid (BALF) cytology was analyzed in both summer (May-August 2017) and winter (November 2017-February 2018). Similar to previous reports, the prevalence of severe EAS in our study population was 10% in summer and 4.3% in winter. The prevalence of mild/moderate EAS was 60% in summer and 87% in winter. The high prevalence of mild/moderate EAS in this population was unexpected, given the 24-hour, year-round pasture environment and the lack of history of respiratory disease. Additionally, 61.1% of horses with both summer and winter data had a different BALF cytology profile between the two seasons. To the authors’ knowledge, this is the first study to use BAL cytology to diagnose, and monitor changes in, EAS phenotype in pastured adult horses. These results help to inform discussions regarding prevalence of EAS in pastured, adult horses in the southeastern region of North America.